Additive Manufacturing of Electrically Conductive Nanocomposites Filled with Carbon Nanotubes. Issue 12 (18th November 2022) - Iervolino, Filippo; Bonessa, Aurora; Foti, Gaia; Levi, Marinella; Suriano, Raffaella
Abstract : Herein, two photopolymers containing multi‐walled carbon nanotubes (MWCNTs) are newly developed to 3D print electrically conductive structures via near‐visible light (405 nm) stereolithography (SL) process. A free‐radical resin and a hybrid cationic/free‐radical photopolymer are used as a matrix and loaded with MWCNTs. A solution mixing method is selected to obtain an optimal MWCNTs dispersion. Rheological and photo‐calorimetric analyses are performed by varying filler concentrations (0.25%, 0.50%, 0.75 wt%) as well as electrical properties of the cured nanocomposites are measured. Rheological characterization indicates the free‐radical resin loaded with the 0.25 wt% of MWCNTs as the most suitable material for the 3D printing of electro‐active systems because it guarantees a rapid and homogenous resin recoating in the vat during the printing of two different layers due to its fluidity. The optimal printing parameters for this photocurable MWCNTs‐loaded resin are found through photosensitivity and photo‐calorimetric analyses. Electrically conductive structures with a conductivity value of 0.0006 S cm −1 are successfully printed, showing the immense potential of these conductive polymeric materials in replacing other standard silicon‐based materials manufactured by conventional 2D lithographic processes for the development of electronic devices and microelectromechanical systems (MEMS). Abstract : Herein, electrically conductive structures are successfully 3D printed by stereolithography, using a newly developed photopolymer composed of a free‐radical resin (Therma) loaded by multi‐walled carbon nanotubes (MWCNTs). By varying MWCNT concentrations (0.25%, 0.50%, 0.75 wt%), the average conductivity ranges from 1 × 10 −4 to 4 × 10 −3 S cm −1 .